Development of case Cataract Service and One Day surgery - Anruechai, Kodchapun; Tepsuwan, Jutatip; Suksataphonlarte, Prasinee (Journal of Vongchavalitkul university, 2020)
Objective: This study aimed to develop a service system of One Day Surgery of Case Cataract Service and to compare results of the pre and post operation of the service system. Method: The research and development method was carried out from July 2017 to September 2019 in Nakornprathom Hospital. Results: Results of the research study revealed that the one day surgery consisted of 4 components 1) guidelines on the day of diagnosis and physical assessment, 2) guidelines for Pre-operative preparation, 3) guidelines for Perioperative day and 4) guideline of activities on the first day Post-operation. The developed service system could reduce number of in-patients from 2,236 cases in 2016 to 1,090 cases 2018 and 1,123. This resulted in less staff work load, lessen over-crowding in the hospital, reducing risk factors such as eye infection or fall after operation. The One Day Surgery model could reduce the hospital inpatient cost for 3,222,822 baht in 2018 and 2,910,411 baht in 2019. Therefore, the hospital can improved the quality of service by getting the maximum value of hospital resources. Patients can easily access the service from the hospital with a shorter period of waiting time resulting in increasing patient satisfaction of the service.